Major health system reforms in 27 European countries in 2018 and 2019. (30th September 2020) - Quentin, W; Polin, K; Hjortland, M; van Ginnekin, E; Maresso, A
Abstract: Background: Countries in Europe are continuously reforming their health care systems. Often similar reforms are happening simultaneously in different countries, and policymakers would benefit from considering reform experiences made abroad. However, no systematic information is available about reforms happening simultaneously across countries. This presentation provides an overview of major health reform trends in Europe in 2018 and 2019. Methods: For the HSPM network's annual meetings in 2018 and 2019, information was collected from national experts on the three most important health reforms in each country happening in that year. In the 2019 survey round, experts were also asked to provide an update on the status of the three reforms they had reported in 2018. Subsequently, all reforms were clustered independently, assigning each reform to one (or several) of 11 categories. Results: In 2018, national experts reported on 78 reforms from 26 European countries. Together, more than one-third of the reforms fell under three clusters: 'coverage & resource generation', 'purchasing & payment' and 'hospital care'. Each of these clusters included reforms from at least nine countries. In 2019, national experts reported 79 reforms from 27 countries. The top clusters were 'primary & ambulatory care' and 'governance', with fourteen and twelve reporting countries respectively. Most 2018 reforms (47/78) were still reported as ongoing in 2019, indicating the complexity of many reforms. More than 20 reforms were reported as implemented, while six reforms were abandoned. Conclusions: Health reforms in different countries often focus on similar topics. Some countries are experimenting with reforms that have already been implemented or abandoned in other countries. There is huge potential for cross-country learning as information on reform experiences may provide inspiration for reforms or help avoid the making the same mistakes in another country.